1990
DOI: 10.1038/345361a0
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for synergistic activation of a mammalian gene by GAL4 derivatives

Abstract: In prokaryotes and eukaryotes many gene activators work synergistically. For example, two dimers of lambda repressor interact to promote binding of these proteins to DNA, a reaction that is crucial at the repressor concentrations found in lysogens. In this case one of the bound dimers activates transcription, evidently by touching RNA polymerase. In another example, the yeast transcriptional activator GAL4, which can stimulate transcription in many eukaryotes, binds to multiple sites on DNA to activate transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
255
0
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(265 citation statements)
references
References 15 publications
9
255
0
1
Order By: Relevance
“…The interaction of acidic activators with multiple general initiation factors (e.g., TFIID, TFIIB, and TFIIH) is compatible with the high degree of synergy that is observed in transcriptional activation (7,11) as discussed by Greenblatt (32) and Herchlag and Johnson (41). Formation of at least a partial open complex and transcriptional initiation on linear DNA do not require TFIIE, TFIIH, or ATP, since RNA polymerase II can synthesize a promoter-specific trinucleotide in the absence of these factors (31).…”
Section: Discussionmentioning
confidence: 79%
“…The interaction of acidic activators with multiple general initiation factors (e.g., TFIID, TFIIB, and TFIIH) is compatible with the high degree of synergy that is observed in transcriptional activation (7,11) as discussed by Greenblatt (32) and Herchlag and Johnson (41). Formation of at least a partial open complex and transcriptional initiation on linear DNA do not require TFIIE, TFIIH, or ATP, since RNA polymerase II can synthesize a promoter-specific trinucleotide in the absence of these factors (31).…”
Section: Discussionmentioning
confidence: 79%
“…pGal 5 -c-myc P2 luciferase was constructed by inserting the PvuII-SacI fragment of pGal 5 -P2 CAT (73) into the SmaI-SacI sites of pGL2 (Promega). pGal 5 -Sp 4 -HIV2 CAT was constructed from pGal 5 -HIV2 CAT (73) by insertion of an oligonucleotide [(GGGGCGGGAC) 4 ] into the XbaI site. pGal 5 -Sp 4 -E1b CAT was constructed by inserting the same oligonucleotide into the XbaI site of pGal 5 -E1b CAT (Gal4/E1bTATA) (41).…”
Section: Methodsmentioning
confidence: 99%
“…In many cases, it is not known why some combinations synergize while others do not. Three mechanisms of transcriptional synergism have been identified: (i) cooperative DNA binding (18), (ii) formation of multiple contacts between activators and GTFs (4,6,42), and (iii) derepression of chromatin templates by displacement of nucleosomes (5). It has also been suggested that synergy could result from the stimulation of different rate-limiting steps in transcription (25).…”
mentioning
confidence: 99%
See 2 more Smart Citations